Inklusi Keuangan Digital di Pondok Pesantren Transformasi Menuju Ekosistem Cashless: Tinjauan Sistematik Literatur Review - Maula Nasrifah; Muhamad Ahsan (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2026)
Digital transformation in Islamic educational institutions, especially Islamic boarding schools, has become a strategic issue in the development of Islamic financial inclusion. This study aims to synthesize empirical and conceptual evidence regarding the model, determinants, and impact of digital financial adoption in Islamic boarding schools through the Systematic Literature Review (SLR) approach. Using the PRISMA 2020 guide and the SPIDER framework, 35 articles indexed by Scopus and other reputable journals published between 2010–2025 were analyzed thematically and descriptively. The results of the synthesis show that the digitization of pesantren is not only a process of technological adoption, but also a social, institutional, and spiritual transformation based on the values of maqāṣid al-sharī'ah. The conceptual model of Pathways to Cashless Ecosystem in Islamic Boarding Schools describes four stages of transformation, namely antecedents (readiness and initial determinants), adoption process (adoption and implementation), integration phase (integration and governance), and outcomes (sustainability and sharia compliance). Factors that determine success include digital infrastructure readiness, student financial literacy, visionary leadership, and strategic partnerships with sharia fintech providers. Financial digitalization in Islamic boarding schools has been proven to improve administrative efficiency, expand financial access, and strengthen transparency in the management of sharia-based social funds. Theoretically, this research contributes through the integration of technology adoption theories (TAM and UTAUT) with Islamic values and institutional ecosystem perspectives, resulting in a multi-level approach to Islamic financial inclusion. Practically, the results of this SLR are the basis for policy makers, pesantren managers, and sharia fintech providers in designing financial digitalization strategies that are inclusive, sustainable, and in accordance with maqāṣid al-sharī'ah.